Bile acid bearing poly (vinyl chloride) nanofibers by combination of CuAAC click chemistry and electrospinning process. (December 2020) - Altinkok, Cagatay; Karabulut, H.R. Ferhat; Tasdelen, M. Atilla; Acik, Gokhan
Graphical abstract: Highlights: Poly (vinyl chloride) nanofibers possessing bile acids are achieved via CuAAC click chemistry and electrospinning process. ncorporation of bile acids onto PVC backbone leads to enhanced WCA, Ton, Tmax and Tg values and electrospinnability. The achieved properties are attributed to the rigid steroid and triazole rings and free OH groups on the final polymers. Abstract: This study aims to deposit most common bile acids such as lithocholic acid (LCA) and chenodeoxycholic acid (CDCA) bearing poly (vinyl chloride) nanofiber (PVC-LCA and PVC-CDCA) coatings on glass slides surface using a combination method by employing copper (I)-catalyzed azide-alkyne cycloaddition 'click' reaction (CuAAC), followed by electrospinning process. The resulted nanofibers and their intermediates are characterized by spectroscopic (FT-IR- 1 H-NMR), thermal (TGA and DSC), wettability (WCA) and morphological (SEM) analyses. Many characterizations reveal that the bile acid functionalized PVC-LCA and PVC-CDCA are successfully achieved by CuAAC between azido-functional PVC (PVC-N3 ) and alkyne end-functional LCA and CDCA (LCA-Alkyne and CDCA-Alkyne) and their nanofibers obtained by electrospinning show efficiently improved thermal behavior, hydrophilicity and morphological features compared to pristine PVC or their granule analogues. Furthermore, the SEM images indicate that the formation of nanoscale, uniform, cylindrical and smooth fibers without free beads. The changeable properties achieved are attributed to the presence of rigid steroid skeleton, triazole rings and free −OH groups on the final polymers. Hence, it is clear that this facile combination procedure is encouraging for scientists working on potential biomedical PVC applications.